FABRIKASI SEL BAHAN BAKAR PADATAN OKSIDA DENGAN MENGGUNAKAN METODE DRY PRESSING - Prima K, Romanus
Solid oxide fuel cell has many advantages compared to any other fuel cell, since it has higher efficiency and low environment impact. In this research, a solid oxide fuel cell unit has been fabricated. The experiments consist of synthesis and characterization of its material, cell fabrication and morphology study, and cell performance test. The cell was built using NiO-SDC (Sm0.2Ce0.8O1.9) composite as anode, LSGM (La0.9Sr0.1Ga0.8Mg0.2O2.85) as electrolyte, and LSFO (La0.8Sr0.2FeO3) as cathode. Each of them was synthesized by solid state reaction, through homogenization, calcinations at 800-1100°C, and sintering stage at 1200-1350°C. Crystal structures were examined using X-ray diffraction measurement, and the results were analyzed by Le Bail method using Rietica software. LSGM has cubic structure belongs to space group Pm3m, while NiO-SDC has cubic structure belongs to space group Fm3m, and LSFO has orthorhombic structure belongs to space group Pbnm. The components were stacked to form a cell by dry pressing method. Cell morphology was observed using Scanning Electron Microscope (SEM), and different porosity at the component was detected between electrolyte and electrodes. Cell performance test has been conducted by determining maximum cell potential in potential cell measurements, while the cell burned by LPG fuel in air exposure, and the result was 514 mV.